The use of the ratio of C-reactive protein to albumin for the diagnosis of pediatric septic arthritis - Ren, Chong; Yuan, Quanwen; Yin, Chunhua; Yao, Feng; Yu, Wentao; Zhang, Fuyong; Wang, Xiaodong (Frontiers in Pediatrics, 2024)
This study aimed to investigate the relationship between the ratio of c-reactive protein to albumin (CAR) and pediatric septic arthritis (PSA).Methods: Clinical and laboratory data were collected. Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive ability of CAR in identifying PSA. Multivariable logistic regression analyses was performed to calculate adjusted odds ratio (OR) with 95% confidence interval (CI).We included 305 patients with PSA (CAR ≤ 0.447, 182 patients; CAR > 0.447, 123 patients) between September 2013 and November 2022. ROC analysis showed that CAR performed best in diagnosing PSA, with an area under curve (AUC) value of 0.828. After adjusted for potential confounders, we found that high CAR was associated with PSA (OR = 6.85, 95% CI: 2.30-20.40, p = 0.001). In sensitivity analyses, subgroups analyses, and propensity score matching, the results remain stable.The CAR (> 0.447) at admission was an independent risk factor for PSA. It is worthy to further investigate this association.